Effectiveness Of Structured Strengthening Protocol Of Thoracic Opener Muscles In Chronic Smokers - Kadam, Sakshi Sachin; Malawade, Mandar (Journal of Neonatal Surgery, 2025)
Background: Chronic smoking impairs pulmonary function by altering respiratory mechanics and reducing thoracic mobility due to postural changes and muscular fatigue. Strengthening thoracic opener muscles may counteract these effects by enhancing chest wall mobility and respiratory efficiency. Objective: To evaluate the effect of an 8-week structured strengthening protocol targeting thoracic opener muscles on pulmonary function in chronic smokers. Methods: Twenty chronic smokers aged 30–50 years participated in this experimental study. Participants underwent a thrice-weekly, 45-minute structured exercise program focusing on thoracic opener muscles. Pulmonary function was assessed using Forced Vital Capacity (FVC), Forced Expiratory Volume in 1 Second (FEV₁), FEV₁/FVC ratio, and Peak Expiratory Flow Rate (PEFR) before and after the intervention. Results: Statistically significant improvements were observed in all outcome measures post-intervention: FEV₁ increased from 2.10 ± 0.35 L to 2.45 ± 0.38 L (p = 0.0002), FVC from 2.90 ± 0.42 L to 3.35 ± 0.40 L (p = 0.0001), FEV₁/FVC ratio from 72.4 ± 5.8% to 75.6 ± 6.0% (p = 0.004), and PEFR from 315 ± 40 L/min to 370 ± 45 L/min (p < 0.0001). Conclusion: The structured thoracic opener muscle strengthening protocol significantly enhanced pulmonary function in chronic smokers. These findings support the inclusion of targeted physiotherapy in pulmonary rehabilitation strategies to mitigate smoking-related respiratory decline.